2017
DOI: 10.1007/s11596-017-1741-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biocompatibility and osseointegration of calcium titanate coating on titanium screws in rabbit femur

Abstract: This study aimed to examine the biocompatibility of calcium titanate (CaTiO) coating prepared by a simplified technique in an attempt to assess the potential of CaTiO coating as an alternative to current implant coating materials. CaTiO-coated titanium screws were implanted with hydroxyapatite (HA)-coated or uncoated titanium screws into medial and lateral femoral condyles of 48 New Zealand white rabbits. Imaging, histomorphometric and biomechanical analyses were employed to evaluate the osseointegration and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“… 98 The results after 12 weeks of implantation were comparable to HAp‐coated and superior to uncoated implants. 98 Ca 2+ deposition in a nano‐porous Ti alloy equally resulted in improved osteoconductivity and overall bone formation at week four and eight after implantation in a rat femur compared to Na + incorporation. The divalent Ca 2+ incorporates deeper into the layer of the nano‐porous structure, enabling a consistent and sustained release over time, leading to a superior bioactivity and increased trabecular bone formation.…”
Section: Impact Of Surface Properties On Osteogenic Process In Vivomentioning
confidence: 82%
See 2 more Smart Citations
“… 98 The results after 12 weeks of implantation were comparable to HAp‐coated and superior to uncoated implants. 98 Ca 2+ deposition in a nano‐porous Ti alloy equally resulted in improved osteoconductivity and overall bone formation at week four and eight after implantation in a rat femur compared to Na + incorporation. The divalent Ca 2+ incorporates deeper into the layer of the nano‐porous structure, enabling a consistent and sustained release over time, leading to a superior bioactivity and increased trabecular bone formation.…”
Section: Impact Of Surface Properties On Osteogenic Process In Vivomentioning
confidence: 82%
“…For example, the incorporation of calcium ions (Ca 2+ ) into the titanium surface enabled the conversion of passive oxide into a bioactive oxide (CaTiO 3 ), which is more favorable for biological interaction. Wang et al reported excellent biocompatibility and osteointegration effects of nano‐bioactive CaTiO 3 coated screws produced via treatment with NaOH and CaCl 2 98 . The results after 12 weeks of implantation were comparable to HAp‐coated and superior to uncoated implants 98 .…”
Section: Impact Of Surface Properties On Osteogenic Process In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to a coating with hydroxyapatite, which does not form an intimate connection with the titanium and shows delamination and unpredictable biodegradation [ 70 , 71 , 72 ], with the consequence of loose implants, the calcium titanate even preserves the surface architecture and roughness of the implant [ 73 ]. Several authors describe the benefit of a calcium titanate layer on titanium implants in cell culture experiments [ 31 , 74 , 75 , 76 , 77 ], in femoral condyle [ 77 , 78 ], and tibia [ 73 ] of rabbits. Unfortunately, we do not see any significant differences in our experiments between the coated and uncoated implants.…”
Section: Discussionmentioning
confidence: 99%
“…Biocompatibility has been the gold standard for any type of implant be it metal, ceramic or even polymer. Another study using calcium titanate coating on titanium screws has also demonstrated the biocompatibility of the material such that it has excellent synergistic properties with osteoblastic cells [ 134 ]. Here we can summarise that knowing and identifying whether metal-ceramics are biocompatible represents a crucial first step for the material to be identified as a biomaterial.…”
Section: Minimal Evaluations Required For New Materials Before CLImentioning
confidence: 99%